2017
DOI: 10.1152/ajpheart.00131.2017
|View full text |Cite
|
Sign up to set email alerts
|

How does pressure overload cause cardiac hypertrophy and dysfunction? High-ouabain affinity cardiac Na+pumps are crucial

Abstract: Left ventricular hypertrophy is frequently observed in hypertensive patients and is believed to be due to the pressure overload and cardiomyocyte stretch. Three recent reports on mice with genetically engineered Na pumps, however, have demonstrated that cardiac ouabain-sensitive α-Na pumps play a key role in the pathogenesis of transaortic constriction-induced hypertrophy. Hypertrophy was delayed/attenuated in mice with mutant, ouabain-resistant α-Na pumps and in mice with cardiac-selective knockout or transge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 124 publications
(169 reference statements)
1
15
0
Order By: Relevance
“…This pathway finally permits the transcription of gene encoding for pro-fibrotic factors [ 45 ], promoting cardiac hypertrophy. Relevant evidences showed that a chronic activation of this complex protein-kinase cascade could finally lead to heart failure [ 46 ]. It was hypothesized that the molecular pathway that leads to organ hypertrophy in vivo was similar to the one described in cultured vascular cells [ 16 ].…”
Section: The Correlation Between Endogenous Ouabain and Organ Damamentioning
confidence: 99%
See 1 more Smart Citation
“…This pathway finally permits the transcription of gene encoding for pro-fibrotic factors [ 45 ], promoting cardiac hypertrophy. Relevant evidences showed that a chronic activation of this complex protein-kinase cascade could finally lead to heart failure [ 46 ]. It was hypothesized that the molecular pathway that leads to organ hypertrophy in vivo was similar to the one described in cultured vascular cells [ 16 ].…”
Section: The Correlation Between Endogenous Ouabain and Organ Damamentioning
confidence: 99%
“…It was assessed that in Rostafuroxin-sensitive patients, there is a decline of systolic blood pressure of 14 mmHg after 4 weeks of treatment [ 65 ]. Nowadays, we do not have data about the effect of Rostafuroxin on the treatment of renal failure and the effects of hypertension on patients with end-stage renal disease, but this compound might have the effect of amelioration of the grade of hypertrophy and heart failure [ 46 ]. The pharmacological profile and the selective mechanism of action of Rostafuroxin make it the prototype of a compound devoid of the cardiovascular and hormonal side effects associated with digitalis and diuretic.…”
Section: The Correlation Between Endogenous Ouabain and Organ Damamentioning
confidence: 99%
“…Diverse studies reported an association between cardiac hypertrophy and the severity of OSA [22, 23]. In addition, it is important to address that RH may lead to cardiac hypertrophy [24].…”
Section: Discussion/conclusionmentioning
confidence: 99%
“…Considering these ndings, it is possible to observe the role of the studied miRNAs in the cardiovascular-related pathways that are also affected by OSA. In addition, it is important to address that RH may lead to cardiac hypertrophy (6). Thus, the studied miRNAs associated with a favorable response to CPAP treatment could be involved in the regulation of such adverse outcome in the long-term.…”
Section: Discussionmentioning
confidence: 99%